Assessment and Case Formulation in Cognitive Behavioural Therapy - Cockx Adrian; Grant Alec; Mills Jem; Townend Michael (Sage, 2008)
An important contribution to the development of cognitive therapy that synthesizes the best of traditional cognitive therapy with important new developments emerging from a range of different areas. Acknowledgements, Foreword, Introduction, Cognitive Behavioral Assessment and Case Formulation, Assessment in CBT: The Ideographic Approach, Process and Related Issues in Cognitive Behavioral Assessment, The Fundamentals of Case Formulation, Key Issues in Cognitive Behavioral Case Formulation, The Transdiagnostic Turn and Models of Assessment and Case Formulation in Action, Case Studies, Ian: A Case Study of Obsessional Compulsive Disorder, Alice: A Case Study of Helping a Client Suffering from Borderline Personality Disorder, An Organizationally Focused Case Study of PTSD, Case Formulation: Cognitive Behavioral Family Therapy, Broadening the Cognitive Behavioral Formulation for Low Self-Esteem: Helping ''Claire'' with her damaged and Broken Self, A Cognitive Behavioral Case Formulation for Distressing Psychosis, Health Anxiety: A Case Study, A Case Study and Formulation of Chronic Depression in a Client with High Self-Criticism, Index.